(untitled) (Historia, 2021)
The Reverend Archibald Lamont -Champion of the Underdog. The Reverend Archibald Lamont dedicated his whole life to improving the position of the underdog, irrespective of his religion, class or race. To him people were merely people and therefore during his term as city councillor he campaigned to improve the position of Durban’s underdogs: the white labourers, the Indians and the blacks. Lamont considered racial discrimination against the Indians and blacks especially unacceptable since it clashed with his religious beliefs and his trust in British Justice, a view which did not endear him to most of the Durban whites, who regarded him as too liberal, and which resulted in his defeat during the provincial and parliamentary elections of 1927 and 1929. Lamont’s election in 1929 as Durban’s mayor therefore came as a surprise. In fact, his election was part of the city council’s campaign to end an effective black boycott of the municipal beer halls. This boycott was a result of the blacks’ dissatisfaction with the harsh municipal administration. By electing a more liberal person, such as Lamont, as mayor it was hoped to give credibility to the municipality’s attempt to end the boycott by following an ambiguous policy of reform and oppression. However, instead of being a mere ceremonial figure, Lamont had his own ideas on reform and justice and during his three years as mayor he succeeded to some extent in improving the position of the blacks. This also brought him into conflict with the city council, The Natal Mercury, and most of the Durban whites, who viewed his efforts on behalf of the blacks with suspicion. Eventually Lamont was defeated in his bid for a fourth term as mayor and the city council subsequently took a more conservative stand on racial issues. In recognition of his efforts to improve the circumstances of the blacks, the new Umlazi black township was named Lamont township (today Lamontville) on black demand. Lamont also received recognition from the white workers of Durban who, as a result of his efforts to improve their economic position, elected him as a member of the provincial council for Greyville in 1932.